Vaccination with prefusion-stabilized respiratory syncytial virus fusion protein elicits antibodies targeting a membrane-proximal epitope - McCool, Ryan S.; Musayev, Maryam; Bush, Sabrina M.; Derrien-Colemyn, Alexandrine; Acreman, Cory M.; Wrapp, Daniel; Ruckwardt, Tracy J.; Graham, Barney S.; Mascola, John R.; McLellan, Jason S. (Journal of virology, 2023)
Respiratory syncytial virus (RSV) causes tens of millions of acute lower respiratory tract infections and millions of hospital admissions globally each year. An antibody repertoire analysis of a human vaccine trial investigating a prefusion-stabilized RSV fusion (F) glycoprotein antigen (DS-Cav1) identified several neutralizing antibody public clonotypes (PCs) in multiple vaccine recipients. Of these, PCs 1 and 2 were found in six out of six and five out of six vaccine recipients, respectively. Whereas PC1 was shown to bind antigenic site V, the binding site and mechanism of action for PC2 were not defined. Here, we expressed and characterized six antibodies from PC2 and one PC2-like antibody, which we found to be prefusion-specific, possess nanomolar affinity for RSV F, and display neutralization IC 50 s of 20–81 ng/mL. Cryo-EM studies for the RSV F:PC2 Fab complex resulted in a 2.7 Å resolution reconstruction, which shows that this clonotype simultaneously recognizes antigenic site I and an uncharacterized, prefusion-F-specific antigenic site consisting of the membrane-proximal stalk of RSV F. Taken together, our results suggest that immunization with DS-Cav1 boosts the production of neutralizing antibodies that target a previously uncharacterized epitope in a newly designated antigenic site VI. Respiratory syncytial virus (RSV) is the leading cause of bronchiolitis and pneumonia in infants, infecting all children by age 5. RSV also causes substantial morbidity and mortality in older adults, and a vaccine for older adults based on a prefusion-stabilized form of the viral F glycoprotein was recently approved by the FDA. Here, we investigate a set of antibodies that belong to the same public clonotype and were isolated from individuals vaccinated with a prefusion-stabilized RSV F protein. Our results reveal that these antibodies are highly potent and recognize a previously uncharacterized antigenic site on the prefusion F protein. Vaccination with prefusion RSV F proteins appears to boost the elicitation of these neutralizing antibodies, which are not commonly elicited by natural infection.